Kontrastivna študija angleških in makedonskih veznikov za izražanje vzročnosti - Stojanovska-Ilievska, Natasha (Slavia Centralis, 2023)
This paper presents the findings of an analysis of English and Macedonian causal conjunctions based on samples of literary texts in both languages and their published translations. In both languages there are conjunctions used exclusively to indicate causality between two clauses (such as because and бидејќи ‘because’), but there are also conjunctions typically used to indicate other relations (such as temporality in the case of since and штом ‘as soon as’, ‘once’) which have developed a causal interpretation over time. The coordinating conjunctions and in English and и ‘and’ in Macedonian can also have a causal interpretation developed by means of implicature (Lyons 1995: 162–163, 286–287) or inferential enrichment (Mauri & Auwera 2012: 383–384).